Internalization of National Identity to Children Amid the Influence of Globalization - Pipi Andriani; Adinda Rahmah Rangkuti; Hasny Delaila; Nepri Handayani (Journal of Contemporary Gender and Child Studies, 2022)
National identity is a characteristic, identity, or signs attached to a person, whether an `organization, group or country that can differentiate one country from another. National identity is closely related to the values, history, and ideals that unite a group by ties. This study aims to introduce and explain the national identity of the Indonesian nation, the influence of globalization on Indonesian national identity, as well as efforts to preserve Indonesian national identity from the effects of globalization by providing insight to the Indonesian people so that they can understand these things through this paper. This study uses a qualitative method with a literature study method. Based on the research, it was found that the national identity of the Indonesian nation is (1) Indonesian as a National Nation, (2) the state flag of Indonesia is the red and white flag, (3) the national anthem of Indonesia is Indonesia Raya, (4) the symbol of the Indonesian state is Pancasila, and so forth. As well as the influence of globalization on the national identity of the Indonesian nation, namely, (1) the waning of a sense of nationalism and patriotism, (2) hedonism, (3) the decline of politeness, and (4) a lack of cooperation and mutual cooperation.